Evaluation of the QuantiFERON®-TB Gold In-Tube Assay and Tuberculin Skin Test for the Diagnosis of Latent Tuberculosis Infection in an Iranian Referral Hospital - Pourakbari, Babak; Yousefi, Korosh; Mahmoudi, Shima; Sadeghi, Reihaneh H.; Mamishi, Setareh (Infectious Disorders - Drug Targets, 2019)
Background: Mycobacterium tuberculosis remains as a vital threat to global health and its diagnosis is still complicated. Since there is no gold standard for the diagnosis of latent tuberculosis infection (LTBI), its diagnosis routinely relies on measurement of host immune responses to M. tuberculosis antigens using the Tuberculin Skin Test (TST) and Interferon-Y Release Assays (IGRAs). Objective: The aim of this study was to evaluate LTBI among hospitalized children and their parents/ guardians as general populations. Methods: A cross-sectional study comparing TST and IGRA for the diagnosis of suspected LTBI was performed in children and their guardians (as general population) in Children Medical Center, an Iranian referral hospital. Results: In this study, 81 patients hospitalized in CMC and 102 patient's guardians were included. A total of 57 patients (70.4%) had performed a TST and were interpreted during the study. Among them, 32 (56%) had a positive test result when a cut-off of 10 mm induration. There were fewer positive IGRA test results than positive TST results (33% versus 56%) in children. Among guardians, TST and IGRA were positive in 41% and 40% respectively. The agreement between the IGRA test and the TST among them was 0.7, while this was as slightly lower in children (0.63). Conclusion: The results of our study indicate that the IGRA test has a higher specificity than TST, especially in children, while the frequency of positive results with both tests in adults was similar. Considering the false positive results reported with the TST, replacement of the IGRA test with TST in children is recommended.
Keywords: Latent tuberculosis infection